Goal Setting in Teams: Goal Clarity and Team Performance in the Public Sector. (December 2018) - van der Hoek, Marieke; Groeneveld, Sandra; Kuipers, Ben
With the rise of performance management, work in the public sector has changed. An output focus has become more common. Other changes include decentralization and managing organizations more horizontally. Setting performance goals and working in teams exemplify these developments. Despite an extensive literature on goal setting, research on goal setting in teams and empirical studies in public organizations have been largely absent. This study contributes to the fields of public management and teamwork by examining whether and under what team conditions clear goals contribute to team performance in the Dutch public sector. Analyses on survey data ( n = 105 teams) show that both goal clarity and self-management positively affect team performance. The effect of goal clarity on team performance is not affected by teamwork though, indicated by insignificant moderation effects of self-management and information elaboration. Suggestions are offered for future research to better understand goal setting in public sector teams.